Authorization of COVID-19 clinical trials: lessons from 2 years of experience of a national competent authority - Vignot, Stéphane; Dhanani, Alban; Sainte-Marie, Isabelle; de Ligniville Lajavardi, Laure; Even, Gwennaelle; Echemann, Muriel; Hulin, Nina; Ménoret, Claire; Maison, Patrick; Ratignier-Carbonneil, Christelle (Frontiers in Pharmacology, 2022)
The COVID-19 pandemic was immediately marked by strong clinical research activity. The French national competent authority presents the data on request for authorisation during the first 2 years of COVID-19 pandemic to inform discussions on future clinical research issues. Applications for authorisation of interventional COVID-19 trials submitted between March 2020 and February 2022 were analysed. Trials on medicinal products were classified according to market authorization status, mechanism of action of the investigational product, target population and clinical context. In two years, 208 clinical trials were submitted. 75% were authorised, 3% refused, 22% withdrawn by the sponsor. Among medicinal products trials, 6% were adaptative, 28% included outpatients and 2% were focused on post COVID-19 symptoms. Vaccines were evaluated in 9% of trials, antivirals in 38% and immunomodulators in 35%; 63% of antiviral and 60% of immunomodulation trials evaluated the repurposing of a marketed drug. The dynamic of authorisation proves the involvement of stakeholders but also illustrates the risk of dispersion of research efforts and the risk of decorrelation between trials and the epidemic evolution. The high rate of withdrawal of authorisation applications could be explained by changes in the sanitary context and by the dropping of some therapeutic approaches. The majority of clinical trials evaluate repurposing strategies and assessment procedures by competent authorities have to mitigate between the knowledge of safety profile of those drugs and the uncertainty in a new clinical context with rapidly evolving knowledge. COVID-19 experience should now support future repurposing strategies and implementation of adaptive trials.